2021
DOI: 10.3390/met11121905
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling Severe Torrefaction of Agricultural Residues to Produce Sustainable Reducing Agents for Non-Ferrous Metallurgy

Abstract: Torrefaction of almond shells and olive stones, which are typically considered agricultural waste in the southern regions of the European Union, was investigated in this work for application as reducing agents in the metallurgical industry. Four different temperatures were tested: 250, 280, 300 and 350 °C. The evolution of the solid yields with the temperature was determined with TGA measurements. This showed that the duration of torrefaction should not exceed 45 min. The kinetic profiles were successfully fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It was processed in the multiple-hearth furnace facility of CEA-Grenoble in France (so-called CENTORRE furnace, Figure 1). As explained by Demey et al [18], two different agricultural residues were studied for their application as reducing agent in the metallurgical industry. The study concluded that both materials had similar values of fixed carbon content and higher heating value (HHV) after being torrefied at 350 • C. However, torrefied olive stones were selected due to their higher availability and lower cost.…”
Section: Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…It was processed in the multiple-hearth furnace facility of CEA-Grenoble in France (so-called CENTORRE furnace, Figure 1). As explained by Demey et al [18], two different agricultural residues were studied for their application as reducing agent in the metallurgical industry. The study concluded that both materials had similar values of fixed carbon content and higher heating value (HHV) after being torrefied at 350 • C. However, torrefied olive stones were selected due to their higher availability and lower cost.…”
Section: Biocharmentioning
confidence: 99%
“…The ignition of 1 g of dry sample under oxygen atmosphere was performed at a pressure of 30 bar. Benzoic acid (Merck, Darmstadt, Germany) was used for calibrating the heat capacity of the calorimeter [18].…”
Section: Calorimetric Analysismentioning
confidence: 99%
“…Since biomass absorbs CO 2 from the atmosphere during their growth, they release the absorbed CO 2 in the reduction process, thus creating a closed loop carbon cycle [15,16]. Several research groups have investigated the use of biomass or biochar as reductant in metal production [10,[17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…From an economic perspective, however, incorporating biomass reducing agents in metallurgical industries cannot currently compete with fossil reductants. On the other hand, this economic disadvantage decreases when higher carbon taxes are imposed [17,26,27].…”
Section: Introductionmentioning
confidence: 99%